Clinical and endoscopic profile of patients with upper gastrointestinal bleeding at tertiary care center of North India - Anand, Deep; Gupta, Rohit; Dhar, Minakshi; Ahuja, Vivek (Journal of Digestive Endoscopy, 2014)
Background: Upper gastrointestinal bleeding (UGIB) is a common medical emergency associated with significant morbidity and mortality. The presentation of bleeding depends on the amount and location of hemorrhage and the endoscopic profile varies according to different etiology. Despite advancements in medical intervention UGIB still carries considerable morbidity, mortality and economic burden on health care system. At present, there is limited epidemiological data on UGIB and associated mortality from India. Aims: The aim was to study clinical, endoscopic profile, and associated mortality in patients presenting with UGIB. Materials and Methods: One hundred and fourteen patients came to Emergency Department with UGIB during the study period and were subjected to endoscopy to identify the etiology. The clinical and endoscopic profile was analyzed and mortality pattern was studied. Results: The mean age of patients was 49 ± 14.26. Majority of them were males (83.33%) and male to female ratio was 5:1. The most common cause of UGIB was portal hypertension related (Esophageal and gastric varices) seen in 56.14% of patients, peptic ulcer-related bleed was seen in 14.91% patients, gastric erosions were responsible for bleed in 12.28% patients, Mallory–Weiss tear was seen in 8.77% cases, gastric malignancy accounted for 4.38% of cases, Dieulafoy’s lesion was responsible for bleed in 1.75% cases and 1.75% had Duodenal polyp. The mortality rate because of UGIB in our cohort of patients was 21.05%. Conclusions: In the present study, variceal bleed was the most common cause of UGIB, followed by peptic ulcer bleed. Overall mortality was seen in 21.05% of cases; however, majority of mortality was seen in portal hypertension related bleeding.
Keywords: Child-turcotte-pugh; international normalized ratio; mortality; portal hypertension; upper gastrointestinal bleeding